Ballistic performance of honeycomb sandwich structures reinforced by functionally graded face plates. (January 2019) - Gunes, Recep; Arslan, Kemal; Apalak, M Kemal; Reddy, JN
This study investigates damage mechanisms and deformation of honeycomb sandwich structures reinforced by functionally graded face plates under ballistic impact. The honeycomb sandwich structure consists of two identical functionally graded face sheets, having different material compositions through the thickness, and an aluminum honeycomb core. The functionally graded face sheets consist of ceramic (SiC) and aluminum (Al 6061) phases. The through-thickness mechanical properties of face sheets are assumed to vary according to a power-law. The locally effective material properties are evaluated using the Mori–Tanaka scheme. The effect of material composition of functionally graded face sheets on the ballistic performance of honeycomb sandwich structures was investigated using the finite element method and the penetration and perforation threshold energy values on ballistic performance and ballistic limit of the sandwich structures are determined. The contribution of the honeycomb core on the ballistic performance of the sandwich structure was evaluated by comparing with spaced plates (without honeycomb core) in terms of the residual velocity, kinetic energy, and damage area.